Wiley IAS 99 interpretation and application of International Accounting Standards 1999 - Epstein, Barry Jay 1946- (John Wiley & Sons, 1999)
The book offers a listing of all relevant IASC standards, including background information and practical guidance on all the traditional U.S. and U.K. GAAP topics that are not covered by IASC standards